Optimization of Antioxidant Activity of Water-Soluble Fraction of Wader Pari Fish (Rasbora Argyrotaenia) Fermentation Using Response Surface Methodology - Safitri Indah Nurcahyaningsih; Sri Winarti; Muhammad Alfid Kurnianto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Rusip processed by fermentation can potentially contain bioactive peptides as antioxidants and antimicrobials. This study aims to optimize the bioactive content in producing rusip from wader pari fish with the Response Surface Methodology (RSM) method. There were 20 recommended formulas based on factors such as sugar concentration, salt concentration, and fermentation duration. The results showed that salt concentration, fermentation duration, and sugar concentration significantly affected antioxidant activity in rusip. The optimal formulation produced involves the addition of liquid palm sugar with a concentration of 11.22%, salt concentration of 15%, and fermentation duration of 8.9 days. Verification of activity response showed results with antioxidant activity of 56.78%.